Surface morphology changes of acrylic resins during finishing and polishing phases - Serra,Glaucio (2013)
INTRODUCTION: The finishing and polishing phases are essential to improve smoothness and shining on the surface of acrylic resins used to make removable orthodontic appliances. A good surface finishing reduces roughness, which facilitates hygiene, prevents staining and provides greater comfort to the patients. OBJECTIVE: The aim of this paper was to analyze the changes on surface morphology of acrylic resins during finishing and polishing phases. METHODS: Thirty discs (10 mm in diameter and 5 mm in length) were made with acrylic resin and randomly divided into ten groups. The control group did not receive any treatment while the other groups received gradual finishing and polishing. The last group received the entire finishing and polishing procedures. Surface morphology was qualitatively analyzed through scanning electron microscopy and quantitatively analyzed through a laser profilometer test. RESULTS: The acrylic resin surfaces without treatment showed bubbles which were not observed in the subsequent phases. Wearing out with multilaminated burs, finishing with wood sandpaper and finishing with water sandpaper resulted in surfaces with decreasing irregularities. The surfaces that were polished with pumice and with low abrasive liquids showed high superficial smoothness. CONCLUSION: Highly smooth acrylic resin surfaces can be obtained after mechanical finishing and polishing performed with multilaminated burs, wood sandpaper, water sandpaper, pumice and low abrasive liquids.